2002
DOI: 10.1076/edre.8.1.87.6920
|View full text |Cite
|
Sign up to set email alerts
|

Behind the High Achievement of East Asian Students

Abstract: Hong Kong, Japan, Korea and Singapore are the only East Asian countries in the Third International Mathematics and Science Study (TIMSS), but students in these 4 countries outperformed their counterparts in the TIMSS mathematics test. An examination of the student background information showed that there was little commonality among the 4 countries which can be used to explain the superior achievement of their students. The only common background data for the 4 places were their high population density and lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 4 publications
7
88
1
6
Order By: Relevance
“…Further, studies have examined the influence of social-cognitive factors on school performance (Casey, Nuttall, & Pezaris, 2001;Ercikan, McCreith, & Lapointe, 2005;Leung, 2002), and the results have suggested that certain social cognitive factors are critical in influencing students' mathematics achievement. Among these, a positive self-concept is frequently posited as a variable that facilitates certain desired outcomes, such as academic achievement (Casey et al, 2001;Ercikan et al, 2005;Kung & Lee, 2016;Marsh, 1990;Marsh, Trautwein, Lüdtke, Köller, & Baumert, 2005;Marsh & Yeung, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have examined the influence of social-cognitive factors on school performance (Casey, Nuttall, & Pezaris, 2001;Ercikan, McCreith, & Lapointe, 2005;Leung, 2002), and the results have suggested that certain social cognitive factors are critical in influencing students' mathematics achievement. Among these, a positive self-concept is frequently posited as a variable that facilitates certain desired outcomes, such as academic achievement (Casey et al, 2001;Ercikan et al, 2005;Kung & Lee, 2016;Marsh, 1990;Marsh, Trautwein, Lüdtke, Köller, & Baumert, 2005;Marsh & Yeung, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Türk öğrencilerinin matematiğe karşı nispeten olumsuz tutum sergilemesinin nedeni arasında Türkiye'deki rekabetçi sınav sistemi gösterilebilir. Çünkü rekabetçi sınav sisteminin ve öğretmenlerin öğrencileri teşvik eksikliğinin öğrencilerin matematik dersine karşı olumsuz tepki geliştirilebilecekleri ifade edilmektedir (Leung, 2002).…”
Section: Sonuçlar Ve Tartişmaunclassified
“…Buna göre öğrencilerin televizyon izleme, bilgisayar oyunu oynama, arkadaşlarla vakit geçirme veya ev işi yapma gibi etkinliklere ayırdıkları zaman arttıkça, yabancı dil başarılarında düşme görülmektedir. Bu durum, ülkemizdeki yabancı dil müfredatının yoğun ve zor olması nedeniyle öğrencilerin okul dışı etkinliklere çok katılmalarının müfredata ve ders ödevlerine yeteri kadar zaman ayırmıyor olmaları ile açıklanabilir; çünkü TIMSS başarı ölçümlerinde üst sıralarda bulunan Singapur, Japonya ve Hong Kong gibi ülkelerde öğrencilerin okul dışı etkinlik olarak spora ayırdıkları zamanın, TIMSS'e katılan diğer ülkelerden daha fazla olduğu görülmektedir (Leung, 2002, Akt. Ceylan ve Berberoğlu, 2007.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Sınıf seviyesindeki faktörlere bakıldığında, müfredat, öğretmenin öğrenci gruplama yöntemleri, sınıf yönetimi, ev ödevleri, öğretmen beklentileri, öğretim yöntemleri, okul dışı öğrenmeye ayrılan zaman gibi faktörlerle öğrencilerin akademik başarıları arasında ilişkilere yönelik pek çok araştırma yapılmıştır (Bettencourt ve DuBois, 2002;Bos ve Kuiper, 2010;Davis-Kean, 2005;Leung, 2002;Valentine, Cooper, Won ve Han, 2010;Zhao, 2013). Öğrenci merkezli öğretim yöntemlerinin, haftalık çizelgede belli derslere ayrılan zamanın, düzenli ve güvenli sınıf ortamlarının akademik başarıyla anlamlı ilişkisi vardır.…”
Section: Introductionunclassified